Catequese especial: uma experiência inclusiva - Jorge, Marcos [UNESP]; Avila, Elizabeth Terezinha de Araujo (My University, 2010)
The aim of this paper is to present an experience of inclusion of individuals with mental disabilities in a religious community in the city of Londrina, north Paraná state. Called here Special Catechesis this was an evangelizing held inside a Catholic Church with the mental disabilities people The project, which five years and five classes per year, allowed the development of a pedagogical action with goals of evangelization and catechesis, where all people were successful. It was also an action to raise the consciousness among parents of these children in order to allow their children could participate in the project. Special Catechesis was evaluated for us as significant experience because it allowed a relative and positive inclusion of the classes in religious and social activities of the local community.

O objetivo deste artigo é apresentar uma experiência de inclusão de portadores de deficiências mentais em uma comunidade religiosa na cidade de Londrina, região norte do estado Paraná. Denominada aqui de Catequese Especial, tratou-se de uma ação evangelizadora realizada no interior de uma igreja de denominação católica com portadores de deficiências mentais. O projeto, que teve a duração de cinco anos com cinco turmas anuais, permitiu o desenvolvimento de uma ação pedagógica com objetivos de evangelização e catequese, onde todos catequizandos obtiveram sucesso. Também foi possível uma ação conscientizadora junto aos pais dessas crianças no sentido de permitir que seus filhos pudessem participar do projeto. Avaliamos a Catequese Especial como experiência significativa pois permitiu uma inclusão relativa e positiva das turmas nas atividades religiosas e sociais da comunidade local
Special catechesis: an inclusive experience
Keywords: Special Education; History of Education - Paraná; Inclusion; Educação Especial; Educação - Inclusão; História da Educação - Paraná